Factors That Influence Susceptibility Vessel Sign in Patients With Acute Stroke Referred for Mechanical Thrombectomy - Dillmann, Manon; Bonnet, Louise; Vuillier, Fabrice; Moulin, Thierry; Biondi, Alessandra; Charbonnier, Guillaume (Frontiers in Neurology, 2022)
Background and Purpose : The presence of a Susceptibility Vessel Sign (SVS) in the acute phase of proximal occlusion ischemic stroke indicates the presence of deoxyhemoglobin in the thrombus. Thrombi composition changes over time. The aim of this study was to investigate whether the absence of SVS is associated with a shorter symptom onset to imaging time. Methods : We retrospectively analyzed all patients referred for mechanical thrombectomy at Besançon University Hospital between 1 January 2015 and 31 December 2020 for whom readable T2*-weighted imaging was available. We compared patient characteristics according to the presence or absence of an SVS. We also studied the subgroup for whom the exact symptom onset time was known. We performed a univariate statistical analysis, then a multivariate analysis on the variables that were statistically significant in the univariate analysis. Results : Of the 389 patients included, 309 (79.4%) were SVS+. We found no significant relationship between SVS- and the time between symptom onset and imaging in the whole cohort. In the multivariate analysis, SVS- was associated with anticoagulant treatment (p <0.01), and SVS+ with age (p 0.023) and carotid terminus occlusion (p=0.042). In the known symptom onset subgroup, SVS- was significantly associated with a shorter symptom onset -imaging time (p<0.001), and this was confirmed in the multivariate analysis (p=0.011; OR 0.911; 95% CI [0.844; 0.972]). Conclusion : In the acute phase of proximal occlusion ischemic stroke, absence of SVS was associated with a shorter symptom onset–imaging time for patients with a known symptom onset time.